Exergoeconomics model for power and chilled water cost rates of gas-fueled district cooling system - Majid, M.A.A. (Research India Publications, 2017)
Many researches have been published related to using exergoeconomic approach to assess the performance of the cogeneration plant and the cost rates of products generated by various thermal systems especially in the cogeneration plant. However, there are no detailed studies that had been carried out in the case of Malaysia, a tropical climate country, due to limited number of cogeneration plants, especially gas-fueled district cooling system. This study is on exergoeconomic analysis of gas-fueled district cooling system. The scope of this study focuses on district cooling plant with gas turbine, heat recovery steam generater and steam absorption chillers. The analysis was based on the first and second laws of thermodynamic principles and the cost rates balance equations. The analysis was based on a case study to determine the energy efficiency, exergy efficiency, exergy of fuel, exergy of product and exergy destruction for the gas turbine, heat recovery steam generator and steam absorption chillers of a gas-fueled DC system. In the analysis, the cost rates of power and chilled water were also calculated. From the analysis, it was noted that a difference of approximately 34 for power cost rates and 67 for chilled water rates, when compared with industrial rates. This shows exergoeconomic method provides a feasible approach for evaluating the performance and cost rates of power and chilled water of the gas-fueled district cooling system. © Research India Publications.